Studi Molecular Docking Senyawa Isoniazid Termodifikasi pada Sintase Asam Mikolat Dinding Sel Mycobacterium Tuberculosis - Buannata, Jordi; Wijianto, Bambang; Arief, Ihsanul (Acta Chimica Asiana, 2024)
Using the isoniazid in antituberculosis therapy can lead to mutations in the KatG and inhA genes of Mycobacterium tuberculosis, resulting in the development of resistance and necessitating modifications to the isoniazid compound. This study aims to assess the potential and level of toxicity of modified compounds, namely 4-pyridine carboxylic acid, pyridine aldehyde, and methyl pyridine, on the mycolic acid receptor through a molecular docking approach. PyRx was employed for the docking process using a protocol with an exhaustiveness of 106 and a center grid box at X=42.424, Y=22.4321, and Z=46.6391. Additionally, the ProTox-II website was used to determine the toxicity level of the test compounds. The results obtained from this research consist of the respective affinity values of the test compounds: -6, -5.4, and -5.2 kcal/mol. The toxicity levels of the test compounds are as follows: class 5, class 4, and class 4. All test compounds interact with amino acids on the target protein, specifically with residue numbers Histidine (HIS A:8), Phenylalanine (PHE A:142) through hydrogen bonding, Leucine (LEU A:95) through pi-Sigma (π) bonding, and Valine (VAL A:12) through pi-Alkyl (π) bonding. In conclusion, the 4-pyridine carboxylic acid compound exhibits potential as a promising drug candidate but comes with a high level of toxicity